Sistemas agrários familiares de base agroecológica - 1º Distrito de Canguçu/RS: uma análise multidimensional para o desenvolvimento rural - Drehmer, Ana Carolina Bilhalva (2020)
The present work presents the family agrarian systems, as an analytical category, in order to think about rural development from the perspective of the territory dimensions. The main objective was to investigate the agroecological process in family agrarian systems, in the 1st District of Canguçu/RS, as a driver of rural development strategies for family agriculture. This is a qualitative research using methodological pluralism as a method of analysis, techniques of semi-structured interviewing and photographic survey for primary data collection. A total of ten farming families, who sell their products in short channels, were interviewed, being them namely: family farmers in agroecological transition by the Feira Sabores da Terra of the Cooperativa União dos Agricultores Familiares de Canguçu; and the consolidated agroecological family farmers – from the Feira Agroecológica da ARPA-SUL by the Associação Regional de Produtores Agroecológicos da Região Sul. The results of the research present that family agrarian systems are characterized from their social, cultural, technical and production elements. Moreover, for the territo¬rial analysis, the approach of the multidimensionality of the territory was adopted, given by the economic-political-cultural-natural dimensions - EPCN. Thus, the natural and environmental dimension is presented from the geographical characterization of the municipality of Canguçu and the analysis of thematic maps; the sociocultural and economic dimension for the rescue of the socio-historical and cultural organization of the Brazilian peasantry and family farming in the municipality of Canguçu, being important to understand the social and cultural practices present in family agrarian systems; the political and institutional dimension by the performance of mediators and government programs relevant to this social category; and, from this, a debate regarding the prospects for rural development can be developed. Thus, the continuities and discontinuities of the peasant past are observed in the research subjects, given the permanence of peasant logics and the ruptures resulting from the process of agricultural modernization. On the other hand, there is the search for the reconstitution of territories and knowledge by articulating strategies related to the agroecological process. Therefore, it can be concluded that there are dynamic processes of rural development of territorial basis, from agroecological production and its commercialization, resulting in improvement in the lives of farmers' families.